Financial analysis of seaweed, Kappaphycus alvarezii, farming business toward farmer’s income development in Minahasa Penninsula, North Sulawesi, Indonesia - Kreckhoff, Reni L.; Ngangi, Edwin L. A. (Universitas Sam Ratulangi, 2018)
This study was carried out in the present farming sites of Kappaphycus alvarezii in Minahasa penninsula, Jayakarsa village of North Minahasa, Sondaken of South Minahasa, Buku Tengah of Southeast Minahasa, and Tumpaan of Minahasa Regencies. It was aimed to know the farming system and financially analyze whether the farming business is feasible or not. Data were collected through observations, questioneers and interviews. Literature reviews and financial analyses were also done to know the revenue, the feasibility of seaweed, K. alvarezii, farming business and its development. The farming system in Minahasa penninsula generally used longline method. It is used because of being resilient to strong wind, cheap, and easily implemented and long lived so that the line could be repeatedly used up to 4-5 years. Financial analyses found that among 4 study sites, the highest B/C ratio was recorded in North Minahasa, 6.06, followed by South Minahasa, 2.75, then Southeast Minahasa and Minahasa, 1.67, and BEP values were also different among regencies. Furthermore, NPV, IRR, ROI and PP of all study sites belonged to feasible criteria for development. Different conditions among regencies resulted from different geographic conditions affected the planting system.